Development and validation of sexual abstinence scale (SAS) (2013)
The Sexual Abstinence Scale (SAS) is designed to assess healthy sexual behaviour among adolescents as a way to reduce the incidence of HIV and other sexually transmitted diseases. This cross sectional study took place in two phases. The first phase comprised of 1030 adolescents randomly selected from senior classes in secondary schools in three out of five local government areas within Ibadan municipality. The second phase had 250 participants also randomly selected from senior secondary classes, items generated for the scale were obtained from an extensive literature review. The content validity of the instrument was confirmed through peer reviews of experts in the field of adolescent sexuality. The internal consistencies for the six sub-scales were .8430 for knowledge of sexual abstinence sub-scale, .8170 for perceived risk of sexual abstinence sub-scale, .6310 for attitude towards sexual abstinence sub-scale, .9380 for perceived benefits of sexual abstinence subscale, .7910 for sexual abstinence self-efficacy sub-scale, .8030 sexual abstinence education sub-scale and .8860 for the full scale. The relevance of this scale to stakeholders in adolescent’s reproductive health behaviour, counsellors, researchers as well as the limitations are discussed.